The effect of carbon content and cooling rate on the structure of boron-rich Fe–B–C alloys - Sukhova, E. V. (Physics and Chemistry of Solid State, 2020)
The structural and phase composition of boron-rich Fe–В–С alloys in the concentration range of 9.0–16.0 % В, 0.001–1.7 % С, Fe – the balance (in wt. %) was investigated in this work. The cooling rate of the alloys was from 10 to 103 К/s. The methods of quantitative metallographic, X-ray, energy dispersive X-ray, and differential thermal analyses were applied. It was established that the maximal solubility of carbon in Fe2B hemiboride does not exceed 0.55 %, and that in FeB monoboride – 0.41 %. The alloys that belong to two-phase peritectic (Fe2(B,C)+Fe(B,C)) region, two-phase peritectic-eutectic (Fe2(B,C)+Fe(B,C)) region, and three-phase peritectic-eutectic (Fe2(B,C)+Fe(B,C)+C) region of the Fe–В–С phase diagram were distinguished depending on their structure. The appearance of an eutectic constituents in the investigated alloys was explained by transition of peritectic reaction L+Fe(В,С)®Fe2(В,С) to eutectic reaction L®Fe(В,С)+Fe2(В,С) within the temperature range of 1623–1583 К in the presence of carbon. With cooling rate increasing from 10 to 103 К/s, structural constituents tended to be fine, their volume fraction changed, microhardness and fracture toughness increased.